The Impact of Urbanization and Industrial Structure on Environmental Pollution in China - Feihong Wang (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The economic growth has promoted the development of China's urbanization as well as optimizing and upgrading its industrial structure. However, the situation of environmental pollution has become increasingly severe. This study examines the relationship between urbanization and industrial structure in China considering 30 provinces from the period 2005-2017. This study uses the panel kink regression model to find two threshold points of urbanization and industrial structure and thereby 3-regime model is considered. Several estimations, namely pooling, fixed, and random, are considered an the Akaike information criterion (AIC) method is used to select the best fit model. According to the empirical test, we find that: (1) The relationship between industrial structure and environmental pollution is nonlinear and shown as an inverted N-shaped. When the industrial structure has upgraded to a certain degree, it can reduce wastewater discharge from environmental pollution. (2) Urbanization is positively related to environmental pollution in three different regimes. Owing to the mode of urbanization development in China, the continuous process has brought more and more pollution to the environment. (3) This paper also considers three control variables, namely trade openness, environmental investment, and technology. Among them, environmental investment and technology has a positive relationship with environmental pollution, while the trade openness has a negative relationship with pollution.